Strong Differential Sandwich Results for Analytic Functions Associated with Wanas Differential Operator - Lafta, Mohammed Hadi; Wanas, Abbas Kareem (Iraqi Journal of Science, 2022)
In this article, we introduce and study two new families of analytic functions by using strong differential subordinations and superordinations associated with Wanas differential operator/. We also give and establish some important properties of these families.